Interleaving paper for soda glass sheets and its manufacturing method
Patent Information
- Application Number
- JP2021212793
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-12-27
AI Technical Summary
【0014】 本発明によれば、ソーダガラス製のガラス板の合紙として用いたときにソーダガラス板にヤケが生じ難いソーダガラス板用合紙及びソーダガラス板用合紙の製造方法を提供することが可能となる。
Smart Images

Figure 0007640447000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an interleaving paper for soda-lime glass plates and a manufacturing method thereof, and more particularly to an interleaving paper for glass plates that is less likely to cause discoloration on glass plates made of soda-lime glass and a manufacturing method thereof. [Background technology]
[0002] Soda lime glass is widely used for architectural glass sheets, automotive glass sheets, display glass sheets, and the like because of its low cost. However, the surfaces of these soda lime glass sheets can become contaminated during storage or transportation on a truck or the like, resulting in product defects.
[0003] This type of contamination occurs when alkaline components dissolved in moisture adsorbed on the glass surface react with acidic components in the air or in the glass plate interleaf paper, resulting in the precipitation of sodium carbonate or calcium carbonate, and as a result, the glass plate surface becomes contaminated and appears cloudy, and the inherent transparency of glass can be lost. This phenomenon is called "discoloration," and is said to be unlikely to occur with relatively expensive glass plates that contain almost no alkaline components, such as alkali-free glass plates and quartz glass plates, which are often used as substrates for electronic devices, but is said to be a common phenomenon with soda glass plates.
[0004] Regarding interleaving paper for glass plates, proposals have been made for the purpose of preventing scratches and contamination on the surface of the glass plate. For example, Patent Document 1 discloses a method for preventing the density of adhesive pitch foreign matter from being 0.07 pieces / m 2 A glass plate package using the following interleaf paper has been proposed. Patent Document 2 proposes an interleaf paper for glass plates having a hot water extraction pH of 3.5 to 6.0. Patent Document 3 proposes that by making the texture of the glass interleaf paper uneven, cushioning properties can be obtained and scratches can be suppressed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-143542 A [Patent Document 2] JP 2017-218718 A [Patent Document 3] JP 2016-14205 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, these slip papers could not completely prevent the occurrence of the above-mentioned tarnishing. In particular, the slip paper described in Patent Document 2 has the risk of exposing the soda glass to acidic substances, which may promote the occurrence of tarnishing. In addition, the proposal in Patent Document 3 has the opposite effect from the viewpoint of preventing tarnishing, since the convex parts come into contact with the glass more strongly, and is therefore not suitable for use.
[0007] The present invention has been made in view of these problems, and an object of the present invention is to provide an interleaf paper for soda lime glass sheets which is less susceptible to discoloration.
[0008] Other objects and advantages of the present invention will become readily apparent to those skilled in the art by reading the following description. [Means for solving the problem]
[0009] In order to solve the above problems, the interleaf paper for soda lime glass sheets of the present invention is an interleaf paper for soda lime glass sheets containing wood pulp as a main component, and is characterized in that the hot water extraction pH measured in accordance with JIS P-8133 is 6.5 to 9.5, and the formation index measured by the total β-ray ground is 0.6 or less. With such a configuration, it is possible to obtain an interleaf paper for soda lime glass sheets that is less likely to discolor.
[0010] In addition, in the interleaving paper for soda-lime glass sheets of the present invention, it is preferable that 50% by mass or more of the wood pulp is bleached hardwood kraft pulp. With such a configuration, the interleaving paper for soda-lime glass sheets can be made more resistant to discoloration.
[0011] Moreover, the interleaving paper for soda lime glass sheets of the present invention preferably has an ash content of 1% or less. With such a constitution, the interleaving paper for soda lime glass sheets can be made more resistant to discoloration.
[0012] The present invention can also be understood as a method for producing interleaf paper for soda lime glass sheets.
[0013] The method for producing interleaving paper for soda lime glass plates according to the present invention comprises the steps of preparing a raw material slurry containing wood pulp, and supplying the raw material slurry to a Fourdrinier single layer papermaking machine under conditions of a pulp concentration of 0.7 mass% or less and a pH of 6.5 to 9.5 to carry out papermaking, characterized in that 50 mass% or more of the wood pulp is bleached hardwood kraft pulp. With this configuration, it is possible to produce interleaving paper for soda lime glass plates that is less likely to discolor. Effect of the Invention
[0014] According to the present invention, it is possible to provide interleaving paper for soda-lime glass plates that is less likely to cause discoloration on the soda-lime glass plates when used as interleaving paper for glass plates made of soda-lime glass, and a method for manufacturing the interleaving paper for soda-lime glass plates. [Brief description of the drawings]
[0015] [Figure 1] 1 is a table showing the composition and physical properties of interleaving papers for soda glass sheets obtained in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will now be described in detail with reference to the embodiments, but the present invention is not limited to these descriptions. The embodiments may be modified in various ways as long as the effects of the present invention are achieved.
[0017] The soda glass plate interleaving paper of the present invention has a hot water extraction pH of 6.5 to 9.5 measured according to JIS P-8133. By setting the hot water extraction pH in this range, it is possible to make it difficult for a soda glass plate to become discolored. The hot water extraction pH is preferably 6.7 to 9.0, and more preferably 7.0 to 8.5. If the hot water extraction pH is less than 6.5, discoloration is likely to occur, and the density of the glass interleaving paper is likely to increase, resulting in a decrease in cushioning properties and making the glass plate more susceptible to scratches. If the hot water extraction pH exceeds 9.5, alkaline substances such as sodium hydroxide remain in the glass interleaving paper, which may result in adhesion to the glass plate and absorption of moisture due to its deliquescent property, corroding the glass and causing discoloration.
[0018] In the present invention, there is no particular limitation on the method for making the hot water extraction pH of the soda glass plate interleaf to 6.5 to 9.5, but as an example, it can be realized by using various alkaline substances. Examples of such alkaline substances include salts of weak acids and strong bases such as water-soluble sodium, calcium carbonate, and sodium hydrogen carbonate. Examples of the method for using such alkaline substances include adding an alkaline substance or its aqueous solution to a pulp slurry before papermaking, and then making paper.
[0019] In the present invention, it is preferable not to add aluminum sulfate, but a small amount may be added if necessary. If aluminum sulfate is used, the papermaking pH will decrease, and as a result, the hot water extraction pH will also decrease, which may not fall within the desired range. In addition, if an excess of alkali such as sodium hydroxide is added to achieve the desired hot water extraction pH after adding a large amount of aluminum sulfate, the resulting salt will be generated in large amounts, and the amount of salt remaining in the glass plate interleaf paper will increase, which may lead to scratches. For this reason, even if aluminum sulfate is added before papermaking as a fixing agent for various chemicals or for the purpose of improving the retention on the papermaking machine, the amount used is preferably 0.5 parts by weight or less based on the pulp, more preferably 0.3 parts by weight or less, and it is most preferable to not add aluminum sulfate.
[0020] The interleaving paper for soda glass sheets in the present invention is mainly composed of wood pulp. The pulp used here is chemical pulp such as LBKP (broadleaf bleached kraft pulp) and NBKP (softwood bleached kraft pulp), mechanical pulp such as GP (groundwood pulp), PGW (pressurized groundwood pulp), RMP (refiner mechanical pulp), TMP (thermo-mechanical pulp), CTMP (chemi-thermo-mechanical pulp), CMP (chemi-mechanical pulp), and CGP (chemi-ground pulp), wood pulp such as DIP (deinked pulp), or non-wood pulp such as kenaf, bagasse, bamboo, and cotton. These may be used alone or in a mixture of two or more kinds in any ratio. Furthermore, synthetic fibers may be used within a range that does not impair the quality. From the viewpoint of environmental conservation, it is more preferable to use ECF (Elemental Chlorine Free) pulp, TCF (Total Chlorine Free) pulp, waste paper pulp, and pulp obtained from planted trees.
[0021] Among these pulps, LBKP is preferred because it has a short fiber length and is suitable for improving the texture. In the present invention, it is preferable to contain LBKP at a ratio of 50% by mass or more relative to the total mass of the pulp, more preferably 90% by mass or more, and most preferably 100% by mass of LBKP. NBKP is preferably blended because the fiber itself is soft like LBKP, but on the other hand, since the fiber length is longer than LBKP, if it is blended in a high amount, the texture will be poor due to entanglement, and the unevenness of the glass plate interleaf paper will increase, and the convex parts will hit the glass surface hard, resulting in scratches. NBKP is preferably 50% by mass or less relative to the total mass of the pulp, more preferably 30% by mass, and even more preferably 10% by mass or less. The pulp is preferably composed of only LBKP and NBKP, and the blending ratio of the two is more preferably LBKP:NBKP=100:0 to 50:50.
[0022] The Canadian Standard Freeness (CSF) of the pulp measured according to JIS P 8121:1995 "Testing Method for Pulp Freeness" is preferably in the range of 200 to 550 ml, more preferably 200 to 350 ml, when the entire amount of the pulp is LBKP. If the freeness is less than 200 ml, the productivity may decrease due to poor drainage on the papermaking machine. On the other hand, if the freeness exceeds 550 ml, the strength of the paper layer decreases, and the paper may break when used as an interleaf paper for glass plates. When NBKP is blended, the freeness is preferably in the range of 400 to 600 ml.
[0023] In the present invention, fillers may be used within the range that does not affect the effects of the invention. Examples of such fillers include light calcium carbonate, heavy calcium carbonate, talc, clay, kaolin, titanium dioxide, aluminum hydroxide, etc., and they may be used alone or in combination of two or more. However, since the use of inorganic mineral fillers may damage the glass plate, it is preferable not to use them.
[0024] In the present invention, in addition to pulp and fillers, paper strength enhancers, sizing agents, bulking agents, retention improvers, drainage improvers, aluminum sulfate, wet paper strength enhancers, coloring dyes, coloring pigments, fluorescent whitening agents, pitch control agents, etc. may be blended according to each product. However, it is preferable not to use components other than pulp, since they may be eluted or adhered to the glass. As mentioned above, an alkaline substance such as sodium hydroxide may be used to set the hot water extraction pH in the desired range. It is preferable not to use acidic substances such as aluminum sulfate, and aluminum sulfate is preferably 0.5 parts by weight or less based on the pulp, more preferably 0.3 parts by weight or less, and most preferably not added.
[0025] In the present invention, a pulp slurry adjusted to an appropriate degree of beating is used as a raw material slurry, and is made into an interleaf paper for soda glass plates by a papermaking machine. As the papermaking machine, a known papermaking machine such as a Fourdrinier papermaking machine, a cylinder papermaking machine, a hybrid former, or a gap former can be used for papermaking. The interleaf paper for soda glass plates may be made of a single layer or a multi-layer of two or more layers, for example, three layers. Here, single layer papermaking is preferred in order to obtain an appropriate interleaf paper for glass plates. The basis weight of the interleaf paper for soda glass plates is 20 to 60 g / m 2 Not only is it relatively small, but the density of single-ply paper is relatively low, so it has cushioning properties and can reduce impact. The density is 0.5 to 0.7 g / cm 3 is preferred.
[0026] In order to improve the surface strength of the interleaving paper for soda-lime glass sheets according to the present invention, a sizing liquid containing a known water-soluble polymer such as starch, polyvinyl alcohol or polyacrylamide may be applied using a size press or the like to the extent that this does not adversely affect the effects of the invention; however, it is preferable that the sizing liquid not be used since there is a risk of the components of the sizing liquid leaching out onto the glass surface.
[0027] The method of drying the interleaf paper for soda lime glass sheets according to the present invention after papermaking is not particularly limited, and known drying methods such as hot air drying, infrared drying, and drum drying can be used, and after drying, smoothing treatment can be performed using a calendar device as necessary. However, since the interleaf paper for soda lime glass sheets according to the present invention is desirably low in density, it is preferable not to perform calendaring.
[0028] The interleaving paper for soda glass sheets according to the present invention has a formation index measured by β-ray ground weight of 0.6 or less, and preferably 0.3 or less. The formation index indicates the local basis weight difference of the paper, and the smaller the value, the smaller the local basis weight difference, and the better the paper is formed. The β-ray ground weight used here is a ground weight using a β-ray radiation source, and indicates the distribution of basis weight (sometimes called basis weight). There are widely used ground weights based on light transmission, but these are not suitable for evaluating local basis weight variations because the pulp components, type and amount of filler, hue, whiteness, degree of beating of pulp, etc. are variable factors. Therefore, in the present invention, the formation index measured by β-ray ground weight is used as an index of formation.
[0029] In order to achieve a formation index of 0.6 or less, it is preferable to set the concentration of the raw material slurry at the inlet of the papermaking machine to 0.7% by mass or less, and more preferably 0.6% by mass or less. The concentration of the raw material slurry can be adjusted by the water content. In addition, in the case of a Fourdrinier papermaking machine, it is preferable to use a shaking device. Since there is a tendency to improve the formation, it is easier to achieve a formation index of 0.6 or less. In order to achieve a formation index of 0.1 or less, it is necessary to further beat the pulp, but this leads to excessive power consumption and reduced productivity due to poor drainage on the papermaking machine, so a formation index of 0.1 is the actual lower limit. Paper with a formation index of 0.6 or less measured using the total β-rays has a small difference in local basis weight, so the difference in local paper hardness (cushioning) is also likely to be small. This makes it easier to distribute the pressure when pressed against glass evenly, making it less likely to contaminate the glass surface and less likely to cause scratches. Furthermore, when the difference in local basis weight of the paper is small, the difference in local moisture content of the paper is also small. If the difference in local moisture content of the paper is large, the amount of moisture that transfers to the glass at the parts with high moisture content when pressed against glass is likely to be large, and the action of acidic components therein is likely to cause "discoloration." However, the interleaving paper for soda-lime glass sheets of the present invention has a formation index of 0.6 or less measured by the total β-rays and a hot water extraction pH of 6.5 to 9.5, which not only reduces the difference in moisture content but also makes the structure less susceptible to the action of acidic components, so "discoloration" is unlikely to occur.
[0030] The interleaving paper for soda-lime glass sheets according to the present invention preferably has a sodium content of 150 ppm or less, more preferably 100 ppm or less. Since sodium is considered to be one of the causes of "discoloration," it is preferable to further reduce the sodium content. Since sodium is contained not only in the sodium compounds added but also in the pulp, the sodium content of the interleaving paper for soda-lime glass sheets is also affected by the sodium content in the pulp. For this reason, in order to reduce the sodium content, it is important not only to avoid using sodium compounds such as sodium hydroxide and sodium chloride as much as possible, but also to select the pulp to be used. The sodium content of the pulp to be used is also preferably 150 ppm or less, more preferably 100 ppm or less.
[0031] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" refer to "parts by mass" and "% by mass", respectively, unless otherwise specified. The number of parts added is a value calculated as a solid content. EXAMPLES
[0032] The present invention will be described in more detail below using examples and comparative examples, but the scope of the present invention is not limited to the examples.
[0033] (1) Measurement of pH of hot water extraction The hot water extraction pH of the interleaf papers for soda lime glass sheets according to each of the Examples and Comparative Examples was measured in accordance with JIS P-8133 (1998).
[0034] (2) Glass transfer test Six sheets of soda glass plate insert paper (240mm x 240mm) according to each Example and Comparative Example were sandwiched one by one between seven sheets of tablet cover glass (240mm x 240mm, thickness 1.1mm, soda glass), and placed in a thermostatic chamber (temperature 60°C, humidity 95%), and the condition of the glass plate surface after 96 hours was observed. Cloudiness and defects indicate the occurrence of discoloration. ◎: No cloudiness or defects on the glass surface. ○: The glass surface is cloudy and almost no defects are visible. △: Slight clouding or defects can be seen on the glass surface. (Lower limit of practical use) ×: The glass surface is cloudy and defects are visible. (Not practical)
[0035] (3) Formation index The unit basis weight of the soda glass sheet interleaf paper according to each of the Examples and Comparative Examples was measured at the following measurement pitch using a Beta Formation Tester manufactured by AMBERTEC, and the basis weight normalized standard deviation (nsd) was used as an index to determine the formation index according to the following calculation formula. Basis weight normalized standard deviation (g / m) 1 / 2 = Standard deviation of basis weight (g / m 2 ) / Basic weight (g / m 2 ) 1 / 2 Measurement conditions: Measurement area 20mm x 20mm, measurement pitch 3.5mm x 3.5mm
[0036] (4) Ash content The ash content of the interleaf papers for soda lime glass sheets according to each of the Examples and Comparative Examples was measured in accordance with JIS P-8251 (2003).
[0037] [Example 1] Sodium hydroxide was added to a pulp slurry of 100 parts of bleached hardwood kraft pulp beaten to a freeness of 250 ml CSF (Canadian Standard Freeness) so that the pH of the hot water extraction was 7.2. The paper was made on a fourdrinier single layer papermaking machine and dried to a basis weight of 45 g / m 2 The pulp slurry concentration at the inlet of the papermaking machine was 0.4%.
[0038] [Example 2] An interleaving paper for soda lime glass sheets according to Example 2 was obtained in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 6.6.
[0039] [Example 3] An interleaving paper for soda lime glass sheets according to Example 3 was obtained in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 6.9.
[0040] [Example 4] An interleaving paper for soda lime glass sheets according to Example 4 was obtained in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 7.1.
[0041] [Example 5] An interleaving paper for soda lime glass sheets according to Example 5 was obtained in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 8.0.
[0042] [Example 6] An interleaving paper for soda lime glass sheets according to Example 6 was obtained in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 8.4.
[0043] [Example 7] Example 7 was prepared in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 9.1, to obtain an interleaf paper for soda lime glass sheets.
[0044] [Example 8] Example 8 was obtained in the same manner as in Example 1, except that 100 parts of hardwood bleached kraft pulp was changed to 90 parts of hardwood bleached kraft pulp and 10 parts of softwood bleached kraft pulp beaten to a freeness of 500 ml CSF.
[0045] [Example 9] Example 9 was obtained in the same manner as in Example 1, except that 100 parts of hardwood bleached kraft pulp was changed to 70 parts of hardwood bleached kraft pulp and 30 parts of softwood bleached kraft pulp beaten to a freeness of 500 ml CSF.
[0046] [Example 10] Example 10 was obtained in the same manner as in Example 1, except that 100 parts of hardwood bleached kraft pulp was changed to 50 parts of hardwood bleached kraft pulp and 50 parts of softwood bleached kraft pulp beaten to a freeness of 500 ml CSF.
[0047] [Example 11] An interleaving paper for soda lime glass sheets according to Example 11 was obtained in the same manner as in Example 1, except that the pulp slurry concentration at the papermaking machine inlet was changed from 0.4% to 0.6%.
[0048] [Example 12] Example 12 was obtained in the same manner as in Example 1, except that 100 parts of hardwood bleached kraft pulp was changed to 20 parts of hardwood bleached kraft pulp and 80 parts of softwood bleached kraft pulp beaten to a freeness of 500 ml CSF.
[0049] [Example 13] Example 13 was obtained in the same manner as in Example 1, except that the pulp slurry concentration at the inlet of the papermaking machine was changed from 0.4% to 0.8%.
[0050] [Example 14] The procedure of Example 1 was repeated except that wet-ground heavy calcium carbonate (Carbital 60, manufactured by Imerys Minerals Japan) was added to the pulp slurry so that the ash content was 0.9%, to obtain an interleaving paper for soda lime glass sheets according to Example 14.
[0051] [Comparative Example 1] Comparative Example 1 was obtained in the same manner as in Example 1, except that the pH of the pulp slurry extracted with hot water was adjusted to 6.1 using aluminum sulfate instead of adding sodium hydroxide, to obtain an interleaf paper for soda-lime glass sheets.
[0052] [Comparative Example 2] An interleaving paper for soda lime glass sheets according to Comparative Example 2 was obtained in the same manner as in Example 1, except that the amount of sodium hydroxide added was changed so that the pH of the hot water extraction of the pulp slurry was 9.7.
[0053] The composition and physical properties of the glass plate interleaving papers obtained in each Example and Comparative Example are shown in Figure 1. As a result of carrying out a transfer test on the glass plate interleaving papers obtained in each Example and Comparative Example, almost no cloudiness or defects were observed on the surface of the glass plate using the glass plate interleaving papers of Examples 1 to 14. On the other hand, in Comparative Example 1, discoloration (white turbidity) was observed on the surface of the soda-lime glass plate due to the influence of the acidic substances in the soda-lime glass plate interleaving paper. In Comparative Example 2, discoloration was observed on the surface of the glass plate, possibly due to residual sodium hydroxide in the soda-lime glass plate interleaving paper.
Claims
1. The interleaf paper for soda lime glass contains wood pulp as a main component, and is characterized in that the pH of hot water extraction measured in accordance with JIS P-8133 is 6.5 to 9.5, and the formation index measured in total for β-rays is 0.6 or less.
2. 2. The interleaving paper for soda-lime glass sheets according to claim 1, characterized in that 50 mass % or more of the wood pulp is bleached hardwood kraft pulp.
3. 3. The interleaving paper for soda glass sheets according to claim 1, wherein the ash content is 1% or less.
4. A method for producing interleaving paper for soda glass sheets, comprising the steps of: preparing a raw material slurry comprising wood pulp; and supplying the raw material slurry to a Fourdrinier single layer papermaking machine under conditions of a pulp concentration of 0.7% by mass or less and a pH of 6.5 to 9.5 to make paper. A method for producing interleaving paper for soda-lime glass sheets, characterized in that 50 mass % or more of the wood pulp is hardwood bleached kraft pulp, and the formation index measured by the total β-ray ground is 0.6 or less.
Citation Information
Patent Citations
Glass plate packing method and glass plate package
JP2008143542A
Slip sheet for glass
JP2009184704A
Glass slip sheet
JP2016014205A
Slip sheet for glass sheet
JP2017218718A
Glass interleaving paper and manufacturing method thereof
JP2020033666A